Isolation and characterization of s-myc, a member of the rat myc gene family. - Sugiyama, A (1989)
A 9-kilobase-pair clone containing a myc-related gene that we have designated s-myc was isolated from a rat genomic library. The entire nucleotide sequence of the cloned DNA was determined, showing that the s-myc gene contains an open reading frame consisting of 1287 base pairs without introns. In vitro transcription-translation analysis of s-myc indicated that this gene produces a protein of approximately 50 kDa. The amino acid sequence predicted from the DNA sequence showed that the s-Myc protein is closely related to the murine N-Myc protein but lacks an acidic amino acid-rich sequence commonly present in the Myc-family proteins. Studies on transfection of s-myc into rat RT4-AC tumor cells revealed that the gene produces a polyadenylylated transcript of approximately 4.7 kilobases and that its high-level expression suppresses the tumor-igenicity of RT4-AC tumor cells in nude mice.